(untitled) (Huellas, 2021)
Global trends aiming at a massive incorporation of renewable energies also point to new energy storage technologies. The production of green hydrogen through the electrolysis of water stands out in this context as one of the most promising alternatives, partaking in multiple national plans. However, technical and environmental studies, as well as the normative frameworks that regulate this emergent activity, are still scarce. Taking into account its potential in the region, particularly in Argentina, the aim of this work is to identify and describe the environmental and regulatory challenges posed by the green hydrogen industry in the country. We start from a description of the extraction method and the usual management practices at the international level, to then address the Argentine case and make a critical analysis with the main environmental guidelines to be taken into account.